Effect of Knowledge Transfer on Economic Sustainability With Network Strength as Moderating - Sarwoto Sarwoto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This study aims to examine the effect of knowledge transfer on sustainability in the agricultural sector in Boyolali district and examine the effect of network strength as a moderating variable in the influence of knowledge transfer on economic sustainability. The data were conducted through a survey using a questionnaire with purposive sampling to 119 heads of farmer group cooperatives in Boyolali district, with a questionnaire level of 98 percent. This study applied a hierarchcal regression to test the research model used. The results show that knowledge transfer has significant influence on economic sustainability in the agricultural sector. Finding knowledge in the context of the agricultural sector in Boyolali district has a relationship that is not in line with economic sustainability. While knowledge sharing carried out positively affects on economic sustainability. The power of knowledge sharing in influencing sustainability is largely determined by the strength of the network they have.